Profiles of worldwide government leaders 2001 - Worldwide Government Directories, Inc. (Washington Keesing's Worldwide, 2001)
Annual.
Keywords: Cabinet officers -- Biography -- Periodicals; Cabinet officers -- Directories; Heads of state -- Biography -- Periodicals; Heads of state -- Directories; Statesmen -- Biography -- Periodicals; Statesmen -- Directories